Development and validation of an instrument to assess the knowledge of general practitioners and pediatricians about photoprotection and solar radiation - Fernanda Mendes Araújo; Julliana Andrade do Carmo; Letícia Diniz Cunha; Igor Monteiro Lima Martins; Airton dos Santos Gon; Antônio Prates Caldeira (Sociedade Brasileira de Dermatologia, 2019)
Abstract Background The knowledge of general practitioners about photoprotection is unknown. Objectives To develop and validate an instrument to evaluate the knowledge of general practitioners and pediatricians about photoprotection, gauging the knowledge of these professionals. Methods The study followed the steps: (1) Literature identification and item elaboration related to the theme; (2) Content validation; (3) Apparent validation; (4) Construct validation: internal consistency analysis and discriminatory analysis; (5) Reliability analysis. In Step 4, the instrument was applied to 217 general practitioners and pediatricians who worked in the host city of the study; the scores were compared with dermatologists scores. Results The final instrument had 41 items and showed satisfactory internal consistency (Cronbach's alpha = 0.780), satisfactory reproducibility and good test-retest reliability (good-to-excellent kappa statistic in more than 60% of items). The discriminatory analysis registered a mean score of 54.1 points for dermatologists and 31.1 points for generalists and pediatricians, from a total of 82 possible points, representing a statistically significant difference (p < 0.001). Generalists and pediatricians demonstrated an understanding of the relationship between excessive sun exposure and skin cancer, but they revealed lack of technical information necessary for their professional practice. Study limitations The instrument evaluates only knowledge, without evaluating the conduct of the participants. Conclusion The results show that the instrument has good internal consistency and good reproducibility. It could be useful in the identification of general practitioners and pediatricians knowledge gaps on the subject, for the subsequent development of training and educational strategies.